Development of Microneedles for Diagnostic and Therapeutics - SARAH MCINTYRE (2023)
This work examines the fabrication and use of polymer microneedles made using an adapted screen printing method and UV curable polymer in both diagnostic and therapeutic applications. Starting with smaller round ended microneedles used only for cosmetics, this work looks at optimising the microneedle shape using this printing fabrication method and penetration efficiency and how the microneedles can be adapted for diagnostics such as cholesterol or chloride and delivery of drugs such as pravastatin. The polymer microneedles were prepared by a highly flexible microlithographic 3D printing (ML3DP) process. This process was a type of stencil printing. The process is adaptable using stencils with different aperture sizes, aperture shapes, the number of sequential depositions and the type of UV curable polymer chosen because it is possible to fabricated in an additive manner. Unlike other fabrication methods, it can easily be scaled up for high volume manufacturing and can be readily adapted to produce microneedles of different shape and size. This reduces the cost of the microneedles compared to those fabricated by etching or small scale printing. The microneedle fabrication process previously used to make rounded tip cylindrical shaped microneedles, was optimised to make sharper microneedles for optimum penetration more suited to drug delivery and diagnostic applications. The optimised microneedles fabricated by ML3DP produced a conical shaped base with a stencil of apertures 400μm in diameter. Evenly spaced print gaps were used to fabricate these microneedles. A tipping stencil of 150μm diameter was used after fabrication of the base and the optimised microneedles reliably produced tips with the average diameter of 8μm. This fabrication method yielded microneedles with on average a penetration efficacy 82.42%. Histology and methylene blue staining were used to illustrate the penetration. These results confirm that the sharpness of the tip is critical in the success of penetration, height and width of the microneedles are also important factors for penetration efficiency. Some polymer microneedles were left uncoated and some metallised using various metals. Compression testing was used to determine suitability of bothmetal coated and uncoated polymer microneedles to withstand penetration forces. For use as diagnostic electrodes the ML3DP microneedles were metallised. Chloride and cholesterol detection were looked at as there are not any current microneedle devices that can detect these analytes. Chloride levels can determine dehydration or cystic fibrosis and cholesterol levels can be an indicator for heart disease. For chloride detection the microneedles were metallised with silver and for detection of glucose or cholesterol the microneedles were metallised with platinum.Silver bar electrodes and silver microneedles successfully determined the concentration of chloride solutions in the required range between 2.5 and 40mM and gave a linear v relationship. Platinum microneedle devices were functionalised for diagnostic application by immobilising glucose oxidase or cholesterol oxidase on the surface and were successful in detecting a range of concentrations of glucose or cholesterol. The linear detection region was between 2.5 and 20mM for glucose and between 1.25 and 15mM for cholesterol which is in line with the concentrations of glucose or cholesterol found in the human body. These ML3DP polymer microneedles were shown to be capable of delivering drugs, such as small molecule drug like calcein and large molecule drugs such as pravastatin through a ’poke and patch’ method. A Franz cell method was utilised to measure drugdiffused through porcine skin into a PBS solution within the cell. These tests showed the polymer microneedles facilitated some delivery through the skin albeit not as good as hypodermic needles and silicon microneedles. Microneedles have the potential to be an important part of point of care devices within diagnostics and drug delivery. These polymer microneedles have shown the possible useof microneedles in diagnostic devices for determining chloride for the diagnostics of dehydration or cystic fibrosis and cholesterol for the monitoring of conditions such as heart disease. These polymer microneedles have also highlighted the use as a drug delivery alternative for drugs such as pravastatin for the treatment of high cholesterol.